Geological exploration in the stockpiles of the Rosita Mine, Nicaragua - Alvarado Martínez, Ezequiel Ernesto (2021)
Mining projects require high investments, and their development or closure is dependent, among other factors, due to the variation in the price of commodities in the international market and due to the depletion of their mining reserves, respectively. The Rosita Mine located in the northeast of Nicaragua is a good example of how the price of metals and other social factors, among others, can affect the development of a mine, and may lead to its final closure, the Rosita Mine began industrial operations at late 1950s and closed in the mid-1970s. The geological and tectonic conditions of Nicaragua have allowed the evolution and location of different types of metallic deposits, characterizing the country as the largest gold producer in Central America during the last century. The Rosita Mine is characterized by a Skarn Cu-Au-Ag deposit located in rocks of the Todos Santos Cretaceous formation, as well as in volcanic rocks that have been cut by intrusives of intermediate and felsic composition of more recent age. At the time of closure of the Rosita Mine, in the surroundings of the Santa Rita pit, considerable volumes of low-grade ore were abandoned, as well as several waste dumps (landfills) that with new exploration methods and technological advances it has been possible to determine their volume and law to define them as mineral resources that can be exploited industrially.